2022
DOI: 10.1029/2022ea002705
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Topography and the Underlying Surface of the Bohai Sea on Wind and Gust Forecasts

Abstract: Wind is defined as the movement of air parcels in a particular direction. The wind speed detected by meteorological instruments increases or decreases suddenly as a result of the different amounts of kinetic energy carried by each air parcel. Peak wind gusts, defined as the maximum based on running mean wind speeds in a short sampling period, are a sudden increase in wind speed caused by air parcels with high kinetic energies (Huschke, 1959). Gusts are closely related to physical parameters such as the mean wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Turbulence may arise from complex topography and may contribute to the strong local characteristics of the wind gusts [11][12][13]. Harper et al [14] reported that the various bottom surface properties of the ocean and land lead to distinct turbulence and wind gusts under diverse substrates (e.g., inland, off-land, off-sea and offshore), indicating that wind gusts have significant sea-land differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulence may arise from complex topography and may contribute to the strong local characteristics of the wind gusts [11][12][13]. Harper et al [14] reported that the various bottom surface properties of the ocean and land lead to distinct turbulence and wind gusts under diverse substrates (e.g., inland, off-land, off-sea and offshore), indicating that wind gusts have significant sea-land differences.…”
Section: Introductionmentioning
confidence: 99%
“…Harper et al [14] reported that the various bottom surface properties of the ocean and land lead to distinct turbulence and wind gusts under diverse substrates (e.g., inland, off-land, off-sea and offshore), indicating that wind gusts have significant sea-land differences. Similarly, Wang et al [13] classified the Bohai Sea and its coastal areas into four regions based on topography and analyzed every region's peak gust climatology through observations. They found that a rough bottom surface stimulated stronger turbulence and increased the peak gust and gust factor.…”
Section: Introductionmentioning
confidence: 99%